2022
DOI: 10.1021/acs.jafc.1c07513
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Lipidomic Analysis of Three Edible Brown Seaweeds Based on Reversed-Phase Liquid Chromatography Coupled with Quadrupole Time-of-Flight Mass Spectrometry

Abstract: A comprehensive lipidomic analysis was performed onto three edible brown seaweeds, namely Laminaria japonica, Undaria pinnatifida, and Scagassum natans, using reversed-phase liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (RPLC−Q-TOF-MS/MS). In total, 675 lipid molecules, including glycolipids (GLs), phospholipids, sphingolipids (SLs), betaine lipids, and glycerolipids, were identified and semiquantified. With the exception of the high content of diacylglycerols found in L. japon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 59 publications
2
30
1
Order By: Relevance
“…Betaine lipids are found in extraplastidial membranes of microalgae and macroalgae. A total of 26 DGTS molecular species were identified and quantified in the four red seaweeds. Different from previously reported brown seaweeds, which contained a high proportion of PUFA-DGTSs with the dominant species being DGTS (18:2/18:2), the four red seaweeds investigated in this study showed a lower desaturation level in the DGTS profile, with DGTS (14:0/16:1), DGTS (16:0/16:1), and DGTS (14:0/18:1) being the most common molecular species. Previous studies on other red seaweeds also showed that DGTS (32:1) was the most abundant molecular species in Chondrus crispus and P.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Betaine lipids are found in extraplastidial membranes of microalgae and macroalgae. A total of 26 DGTS molecular species were identified and quantified in the four red seaweeds. Different from previously reported brown seaweeds, which contained a high proportion of PUFA-DGTSs with the dominant species being DGTS (18:2/18:2), the four red seaweeds investigated in this study showed a lower desaturation level in the DGTS profile, with DGTS (14:0/16:1), DGTS (16:0/16:1), and DGTS (14:0/18:1) being the most common molecular species. Previous studies on other red seaweeds also showed that DGTS (32:1) was the most abundant molecular species in Chondrus crispus and P.…”
Section: Resultscontrasting
confidence: 99%
“…The FA composition of GlcADGs in bacteria, fungi, higher plants, and seagrass are mainly composed of C16 and C18 FAs with different unsaturation levels; ,, in contrast, the seaweeds here had a very different acGlcADG profile with arachidonic acid (AA) and EPA constituting a high proportion. Compared with brown seaweeds, red seaweeds contained more GlcADG and acGlcADG molecular species; the highest content and number of molecular species of GlcADG (0.4 nmol/mg, 10 species) and acGlcADG (0.5 nmol/mg, 21 species) were detected in G. amansii.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Sterols are the least abundant lipids in all the species. Seaweeds are reported to show excellent nutritional properties owing to the abundance of GLs in seaweeds, such as kombu, sea mustard, and laver, including high levels of fiber in kombu, and our results are consistent with these reports [ 7 , 20 , 32 , 33 , 34 ]. Furthermore, the nutritional quality of the seaweeds was assessed based on the levels of free fatty acids using the formulas reported earlier [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 92%
“…Hence, they are widely used in the development of food products with enhanced shelf life and quality [ 17 , 18 ]. Nevertheless, seaweeds also have complex lipids, such as glycerolipids (GLs), glycerophospholipids (GPs), and sterols [ 19 , 20 ], and display unique features, such as esterification with ω-3 fatty acids, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) which are not found in terrestrial plants. GPs and GLs play structural roles in biological systems, including the formation of cytoplasmatic and chloroplast membranes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%